Heterogeneity Analysis of Regional Greenhouse Gas Driving Effects: An Empirical Study from Southeast Asian Countries - Wei Deng; Qingquan Liang; Shuai Yan; Xiaodan Shen; Lan Yi (Energies)
Southeast Asia is suffering from extreme weather, and its carbon emissions are increasing rapidly. For efficient emission reduction, clarifying the complex sources behind is necessary. This study takes a new perspective of incorporating multiple GHGs (greenhouse gases) into the same analysis framework, employing the STIRPAT model to dissect the contributions of various socio-economic factors to the emissions of CO2, CH4, and F-gases based on panel data. The analysis reveals that the driving coefficients of total population and urbanization rate are several to 10 times higher than those of other factors and can reach up to 2.98 and 4.715 and are the most significant drivers of GHG emissions in the region. Quadratic per capita GDP shows a significant positive driving effect, indicating that most Southeast Asian countries are unlikely to reach the Kuznets point in current development trajectories. The driving coefficients of F-gases in industrialized countries are significantly higher than those of other GHGs, indicating that their growth rate of F-gases will outpace that of CO2 and CH4. In countries with a similar industrial structure, the driving coefficient of CO2 from the secondary industry is up to 0.183 and down to 0.057, shows the influence of specific sector composition in the secondary industry on emissions. These findings provide critical insights for Southeast Asian policymakers aiming to develop effective climate policies.